KENDALA GURU DAN SISWA DALAM MENERAPKAN SISTEM BELAJAR ONLINE PADA MASA COVID-19 DI SDN 101747 KLUMPANG KEBUN KECAMATAN HAMPARAN PERAK KABUPATEN DELI SERDANG - Mei Lyna Girsang; Maria Friska Nainggolan; Mery Silalahi; Nurul Sari Wahyuni (Fakultas Ilmu Pendidikan Universitas Sari Mutiara Indonesia, 2020)
This study aims to determine the constraints of teachers in implementing the online learning system during the Covid-19 period at SDN 101747 Klumpang Kebun, Hamparan Perak District, Deli Serdang Regency. This type of research is descriptive qualitative research using primary data sources. Data collection used a written interview test to determine the teacher's constraints. Data were analyzed using qualitative data analysis consisting of data reduction, data presentation and conclusions. The results of this study indicate that the obstacles faced by teachers in online learning during the Covid-19 pandemic are the limitations of teachers in using online learning applications so that the learning process is not optimal, students who do not have Android and computers and the availability of internet packages. This causes the learning process not optimal and students do not understand the material presented by the teacher